(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2011)
This article proposes an ethics for service delivery. The proposal is framed within the context of a reformed paradigm. The application is in the modern organisation culture. The design for the ethics for service delivery originates in the obedience man has towards the cultural mandate. Obedience generates man to be responsible for and exercise care for people and structures. This forms part of man’s calling in this world. In addition to this, service should be de livered to exercise value-based work, to promote justice and to avoid power abuse. With this in mind, the authors suggest that organisations should consider their actions towards their employees and the customers they serve. In this scenario two aspects are prominent: the ethical behaviour (of employees and employers) and the service rendered to customers. The principles that underlie ethics and service delivery should be entrenched into the culture of an organisation and form part of the acceptable behaviour expected from individuals. Within this epistemology this article provides guidelines for the development of a reformed ethical service delivery approach.